2004
DOI: 10.1016/j.ccr.2004.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The Sema domain of Met is necessary for receptor dimerization and activation

Abstract: Hepatocyte growth factor (HGF) binds the extracellular domain and activates the Met receptor to induce mitogenesis, morphogenesis, and motility. The extracellular domain of Met is comprised of Sema, PSI, and four IPT subdomains. We investigated the contribution of these subdomains to Met receptor dimerization. Our observations indicate that the Sema domain is necessary for dimerization in addition to HGF binding. Treatment of Met-overexpressing tumor cells with recombinant Sema in the presence or absence of HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
167
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(174 citation statements)
references
References 62 publications
6
167
0
1
Order By: Relevance
“…Recent studies also reported that c-Met/ HGF signaling induces aberrant cellular activities such as cell proliferation, motility, disassociation and morphological change, which can be effectively blocked by the antagonistic fragment of HGF/SF (NK4) [15][16][17] or by c-Met decoys, referring to the soluble truncated form of c-Met. [18][19][20] The soluble truncated form of c-Met competitively binds to HGF instead 3 Gastric cancer cases who diagnosed between 2 and 9 years from cohort enrollment. 4 Gastric cancer cases who diagnosed within 1 year from cohort enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also reported that c-Met/ HGF signaling induces aberrant cellular activities such as cell proliferation, motility, disassociation and morphological change, which can be effectively blocked by the antagonistic fragment of HGF/SF (NK4) [15][16][17] or by c-Met decoys, referring to the soluble truncated form of c-Met. [18][19][20] The soluble truncated form of c-Met competitively binds to HGF instead 3 Gastric cancer cases who diagnosed between 2 and 9 years from cohort enrollment. 4 Gastric cancer cases who diagnosed within 1 year from cohort enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…This experimental system is remarkably different from the inhibitory strategies developed so far, since it allows evaluation of the cell-autonomous effect of oncogene inhibition, independently from the perturbation of the tumor microenvironment. In fact, conventional inhibitors of MET-such as small tyrosine kinase inhibitors, antibodies or decoy molecules (Christensen et al, 2003;Kong-Beltran et al, 2004;Michieli et al, 2004;Petrelli et al, 2006;Smolen et al, 2006)-impair the activity of the receptor not only in tumors but also in host cells. This is critical, since MET functions have been linked also to neo-angiogenesis and host defense responses, as this oncogene is expressed in endothelial cells as well as in macrophages and in cells of the immune system (Bussolino et al, 1992;Galimi et al, 2001;Skibinski et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Onartuzumab is a recombinant, humanized, monovalent monoclonal antibody that binds to the SEMA domain of Met thereby blocking HGF binding and subsequent Met activation (12,13). In preclinical studies, inhibition of Met signaling with onartuzumab results in pathway suppression and blockade of ligand-induced cell proliferation, migration, invasion, and cell survival (13,14).…”
Section: Introductionmentioning
confidence: 99%